BANGUNAN KANTOR MULTIFUNGSI DI TANAH ABANG - Annissa Nur Sofura; Petrus Rudi Kasimun (Jurusan Arsitektur dan Perencanaan, 2019)
Millennials is still a very hot topic to discuss. The many problems in this generation make most people research and find ways to overcome these things. On this occasion, the millennial generation problem that will be chosen to be solved with architectural products is the productive age. This productive age is the background of the main activity of the millennial generation, which is working. Many studies also say that this work is the cause of the highest level of stress occurring in this generation. After being examined more deeply, not because it has to work which is the main reason for the stress level to occur in millennials, but the conditions and work systems that are not in accordance with the criteria of that generation. Therefore, the